Critical ranges of leaf micronutrient levels in coffee seedlings (Coffea arabica L.) - Gontijo, Roger Alexandre Nogueira; Carvalho, Janice Guedes de; Guimarães, Rubens José; Mendes, Antônio Nazareno Guimarães; Andrade, Wander Eustáquio de Bastos (Coffee Science - ISSN 1984-3909)
The objective of this work was to quantify the leaf micronutrient levels in coffee seedlings, to establish critical ranges in the experiment carried out in Federal University of Lavras, from May/2002 to January/2003. A random block design was arranged in a 6 x 4 factorial scheme (six fertilization levels and four sampling times), with four replications (nine plants were evaluated per plot). The evaluations were performed when the seedlings reached the stages of 3, 4, 5 and 6 pairs of leaves. The fertilization levels used were: 25%, 50%, 75%, 100%, 125%, and 150% with standard substrate). The following characteristics were evaluated: plant height, shoot diameter, leaf area, root dry weight, shoot and leaf dry weight’s, and chemical analysis of the leaves to quantify the B, Cu, Fe, Mn, and Zn levels. To determine the critical ranges, the most adequate mathematical model to the fertilization levels in relation to plant performance was selected. For this purpose, where there was a significant effect of the fertilization level and of the interaction between time and fertilization level, regression analyses of each characteristic evaluated in each sampling time were performed. The same process was applied to the leaf micronutrient levels found in leaf dry weight, interpolated with the fertilization levels. Then the regression equations set for each characteristic in each sampling time were derived to determine the point of maximum performance. Using the equations it was possible to identify the ranges of the fertilization substrate levels that provided a maximum performance above 90% in the plants. These fertilization levels were substituted in the regression equations of the leaf micronutrient levels in each sampling time to find the critical range of micronutrients (mg/kg) : boron (39,74 to 39,94), copper (6,94 to 9,29), iron (209,01 to 213,88), manganese (33,05 to 37,21), zinc (3,68 to 4,08). The optimum stage to harvest leaves is four pairs of leaves.